Direct conversion receiver for active integrated antenna - Jamaluddin, Mohd. Haizal (2005)
This thesis describes the design of a compact miniature and low cost microstrip dipole antenna integrated with 900 hybrid coupler, oscillator and diodes for direct conversion, or zero IF receiver. The frequency chosen is at 2.4 GHz, which is of particular interest for RFID application. In this receiver design, Agilent’s ADS software using momentum simulation and circuit simulation is employed to analyze the entire structure. In the fabrication process, the proposed receiver element is printed on a FR4 substrate with a dielectric constant of 4.7, a thickness of 1.6 mm and a conductor loss of 0.019. Microstrip dipole antenna that is presented here has a wide bandwidth up to 24% bandwidth. The 900 hybrid coupler can act as a phase shifter to provide the necessary 900 characteristics to operate with I/Q signal for direct conversions. Two schottky diodes (HSMS 8101) are mounted onto each of two coupler’s output port to act as a mixer. One kHz sinusoidal signal act as a baseband have been generated and modulated using signal generator. The demodulated signal is detected using direct conversion receiver circuit and the baseband signal at the output ports should be detected using oscilloscope